Condições de saúde bucal em pessoas de 60 anos ou mais no Município de São Paulo (Brasil) - Rosa, Antonio Galvão Fortuna (1992)
The oral health status of people aged 60 years or over in S. Paulo in 1989 is discussed. According to data relating to dental caries, periodontal diseases, need and use of prothesis and prevalence of hard and soft oral tissue pathologies, this study concludes that elder people present a very bad oral health status. The definition of a policy and dental care programs addressed to the aged are recommended.